An overview on the developing trend of pulsating heat pipe and its performance. (August 2018) - Bastakoti, Durga; Zhang, Hongna; Li, Da; Cai, Weihua; Li, Fengchen
Highlights: Developing trend of pulsating heat pipe and its performance are overviewed. Works on thermal performance of PHP in the past five years are mainly summarized. Effects of various parameters on PHP and its working mechanisms are focused on. Abstract: The world is running against time to develop enough source of sustainable energy. Producing a viable and eco-friendly energy source is one part of the solving the energy crisis, and managing it efficiently is another. Since the development of Pulsating Heat Pipe (PHP) in early 1990s, it has gained a lot of attention as potential heat management system that is passive, efficient, compact yet simple, and could address the issues related to higher heat flux in micro-electronic devices. Researchers have been working on not only to develop the advanced form of the PHP, but also in understanding the working phenomenon of operational heat pipe. With the introduction of different kinds of working conditions for the operation of the device, including the geometric parameters, orientation, heat input, and other operational parameters, researches have revealed many functioning and non-functioning features which are very complex. Introduction of various kinds of fluids as the working material for the PHP have yielded different responses by the system at different fill ratio (FR). Though many scientists have worked day and night to fully understand the thermo-physical behavior through experimental investigation, numerical and computational approach and theoretical approach, full-fledge understanding of the operational mechanism is not yet achieved. This is due to the involvement of complex coupling effect of hydrodynamic and thermodynamic features, and the presence of liquid-slug and vapor-plug system. Nevertheless PHP has found many potential application fields in the area of thermal management. In recent years, researches on PHP have shifted from conventional investigation to newer dimensions that include use of non-conventional working fluids, visualization techniques, and rigorous computational works. This review paper is mainly focused on the results of experimental and numerical works done by researchers in the recent past. Authors believe that this paper will be very useful for future researchers to understand the recent trends in this arena better. This paper also exposes the latest works on PHP with potential and promising applications in novel field of thermal management.